Mengungkap Arti Perilaku Etis Menurut Fresh Graduate Akuntansi - Khoirin Azaro; Kurnia Ekasari; Kartika Dewi Sri Susilowati (Journal of Applied Accounting and Taxation, 2020)
This is the field of study that deals with accounting ethics. This turns out to be even more problematic because the emergence of cases involving the accounting profession within a few years has disfigured the credibility of the accounting profession. Every ethical or unethical behavior carried out by accountants depends on each individual. One of the simplest ways of tackling this problem is the presence of education about ethical awareness of accounting skills, especially in a business context that requires relevant reporting. The overall goal of this work was to find out how the meaning of ethical behavior according to accounting fresh graduates. This study uses qualitative approach through interpretative. For this study, we analyzed the data collected from interview. There were 4 participants in this research. From the results, it is clear that ethics in concept and practice is not much different and ethics is something that must appear in every aspect of life. Ethics must be present in individuals and ethics becomes important in the work as a basis for take an action. This conclusion follows from the fact that ethics education influences the accounting practices of fresh graduate accounting.